Implementasi Kegiatan Pengabdian Masyarakat dalam Pembentukan Migas Center Universitas Sriwijaya - Adianto, Mohamad Obby; Gustama, Muhammad Agni; Ar-rouf, Ferdian Budi; Utami, Nyimas Ulfatry; Afifah, Putri Dwi (Al-DYAS, 2026)
The oil and gas sector is one of the main pillars of the national economy and is currently facing the challenge of declining production, making the enhancement of human resource (HR) quality in the upstream oil and gas industry a strategic necessity. The core problem lies in the absence of optimal synergy between the oil and gas industry and the education sector, as reflected in the mismatch between higher education graduates’ competencies and industry needs, including in the South Sumatra Region (Sumatera Bagian Selatan, Sumbagsel), which comprises South Sumatra, Jambi, Bengkulu, and Bangka Belitung Provinces. This study aims to describe the establishment and role of Migas Center UNSRI as a form of community service in improving oil and gas HR competencies in the Sumbagsel region through collaboration between Universitas Sriwijaya and SKK Migas Sumbagsel. A descriptive qualitative approach was employed to examine the implementation of community empowerment policies and the mapping of upstream oil and gas industry needs at the regional level. The findings show that the collaboration between Universitas Sriwijaya and SKK Migas Sumbagsel resulted in an agreement to establish Migas Center UNSRI as a center for research and training in oil and gas management in South Sumatra. The existence of Migas Center provides the education sector with a clearer picture of industry requirements, including the importance of establishing study centers and certification bodies located in Sumbagsel so that companies do not have to rely on facilities in Java. Conceptually, Migas Center UNSRI is positioned as the forerunner of the establishment of a Petroleum Engineering Department at Universitas Sriwijaya as well as an instrument for strengthening the capacity of local human resources in the oil and gas sector.